Ablation of the spindle assembly checkpoint by a compound targeting Mps1 - Schmidt, Marc (2005)
The spindle assembly checkpoint ensures accurate chromosome segregation by delaying anaphase initiation until all chromosomes are properly attached to the mitotic spindle. Here, we show that the previously reported c-Jun amino-terminal kinase (JNK) inhibitor SP600125 effectively disrupts spindle checkpoint function in a JNK-independent fashion. SP600125 potently inhibits activity of the mitotic checkpoint kinase monopolar spindle 1 (Mps1) in vitro and triggers efficient progression through a mitotic arrest imposed by spindle poisons. Importantly, expression of an Mps1 mutant protein refractory to SP600125-mediated inhibition restores spindle checkpoint function in the presence of SP600125, showing that its mitotic phenotype is induced by Mps1 inhibition in vivo. Remarkably, primary human cells are largely resistant to the checkpoint-inactivating action of SP600125, suggesting the existence of Mps1-independent checkpoint pathways that are compromised in tumour cells.